Design of a Thermoelectric Cool Box with Electronic Mobile-Based Temperature Control and Monitoring System - Moh. Abdul Gofur; Rahajeng Kurnianingtyas; Fauzan Amri; Rofan Aziz (Berkala Sainstek)
Temperature control in a thermoelectric coolbox is important for maintaining the freshness and quality of stored items. This research aims to design a temperature control and monitoring system for a thermoelectric coolbox based on mobile electronics using the Wemos D1 R32 microcontroller and the Blynk application. The system uses the DHT11 sensor to detect temperature and humidity inside the coolbox. Data from the sensor is transmitted in real-time to the Wemos D1 R32 microcontroller, which then forwards it to the Blynk application via Wi-Fi. Users can monitor temperature, humidity, and control the coolbox's cooling function through the Blynk application on their mobile devices. This system is expected to provide an efficient solution for temperature management and improve user comfort. The test results show that the system can provide accurate and responsive temperature control, with an easy-to-use interface. The research uses 4 peltier elements, which have two different sides: hot and cold. The cold side of the peltier is used for storing mangoes, with a storage temperature between 10-15 oC. The test results show the temperature reached 14oC within 1 hour. In the automatic control system, the fan inside the cabin will turn off when the temperature reaches 14 oC and turn on again when the temperature exceeds 15 oC. Without control, the temperature of the mangoes was recorded at 11.6 oC and kept cooling, while with control, the temperature of the mangoes remained stable at 14.5 oC. This system is effective in maintaining optimal storage conditions.